Mechanisms of output interference in cued recall. - Wilson, Jack H.; Kellen, David; Criss, Amy H. (Memory & Cognition, 2020)
The primary aim of this paper is to elucidate the mechanisms governing output interference in cued recall. Output interference describes the phenomenon where accuracy decrease over the course of an episodic memory test. Output inference in cued recall takes the form of a decrease in correct and intrusion responses and an increase in failures to response across the test. This pattern can only be accounted for by a model with two complementary mechanisms: learning during retrieval and a response filter that prevents repeated recall of the same item. We investigate how a retrieval filter might operate by manipulating the similarity of words. The data are consistent with a retrieval filter that does not operate by a global match of a potential target to previously recalled items. Results are discussed within the search of associative memory theory.